Arabic Interference in Manuscript of Hadza Kitab Mujarrobat: A Study of Arabic Philology and Sociolinguistics - Ardiansyah, Ardiansyah; Sahrani, Sahrani; Izzati, Dinda (Institut Agama Islam Negeri Curup, 2024)
This research aims to describe the manuscript of the Hadza Kitab Mujarrobat and reveal the form of Arabic interference found in the manuscript of the Mujarrobat. This research uses a descriptive mix methode with two analysis tools, namely philology and sociolinguistics. This study uses Weinreich's interference theory which applies three types of interference. The Hadza Kitab Mujarrobat manuscript uses Malay Pegon Arabic script printed in 1317 AH. There are several holes caused by termites, and it uses simple illumination and has a colophon. The use of Arabic interference in the manuscript of the Hadza Kitab Mujarobat in the form of prayers (141 times), propositions (7 times), names (39 times), opening words (5 times), subtitles (48 times) and expressions Islamic (33 times). Meanwhile, the use of interference from Arabic lingual elements in the manuscript of the Hadza Kitab Mujarobat uses the form of Arabic paragraphs (41 times), Arabic sentences (118 times), Arabic phrases (158 times), and Arabic words (93 times).